Analisis Butir Soal Biologi Kelas VIII Madrasah Tsanawiyah Negeri 6 Kerinci Menggunakan Program Komputer Anates 4.0 For Windows - Winda Ayu Fietri; Lufri - -; Syamsurizal - -; Zulyusri - - (Undiksha, 2021)
This study aims to see the quality of the items of Biology class VIII Madrasah Tsanawiyah Negeri 6 Kerinci about the respiration system using the Anates version 4. This research uses a quantitative descriptive approach and data analysis techniques are carried out by using a test technique in the form of questions about the respiration system in question. item in multiple choice form. The population in this study were all students of class VIII Kerinci as many as 40 students. The sampling technique used was simple random sampling. Data analysis used Anates version 4 computer program for windows. The results showed that the level of validity of the questions was 0.43; the reliability level of the questions is high, namely 0.61; sufficient distinguishing power, namely 36%; medium difficulty level, namely 88%; and the quality of the outwit is 100% excellent.